A global analysis of multitrial data investigating quality of life and symptoms as prognostic factors for survival in different tumor sites. Issue 2 (11th October 2013) - Quinten, Chantal; Martinelli, Francesca; Coens, Corneel; Sprangers, Mirjam A. G.; Ringash, Jolie; Gotay, Carolyn; Bjordal, Kristin; Greimel, Eva; Reeve, Bryce B.; Maringwa, John; Ediebah, Divine E.; Zikos, Efstathios; et al.
Abstract : BACKGROUND: The objective of this study was to examine the prognostic value of baseline health‐related quality of life (HRQOL) for survival with regard to different cancer sites using 1 standardized and validated patient self‐assessment tool. METHODS: In total, 11 different cancer sites pooled from 30 European Organization for Research and Treatment of Cancer (EORTC) randomized controlled trials were selected for this study. For each cancer site, univariate and multivariate Cox proportional hazards modeling was used to assess the prognostic value ( P  < .05) of 15 HRQOL parameters using the EORTC Core Quality of Life Questionnaire (QLQ‐C30). Models were adjusted for age, sex, and World Health Organization performance status and were stratified by distant metastasis. RESULTS: In total, 7417 patients completed the EORTC QLQ‐C30 before randomization. In brain cancer, cognitive functioning was predictive for survival; in breast cancer, physical functioning, emotional functioning, global health status, and nausea and vomiting were predictive for survival; in colorectal cancer, physical functioning, nausea and vomiting, pain, and appetite loss were predictive for survival; in esophageal cancer, physical functioning and social functioning were predictive for survival; in head and neck cancer, emotional functioning, nausea and vomiting, and dyspnea were predictive for survival; in lung cancer, physical functioning and pain were predictive for survival; in melanoma, physical functioning was predictive for survival; in ovarian cancer, nausea and vomiting were predictive for survival; in pancreatic cancer, global health status was predictive for survival; in prostate cancer, role functioning and appetite loss were predictive for survival; and, in testis cancer, role functioning was predictive for survival. CONCLUSIONS: The current results demonstrated that, for each cancer site, at least 1 HRQOL domain provided prognostic information that was additive over and above clinical and sociodemographic variables. Cancer 2014;120:302–311 . © 2013 American Cancer Society . Abstract : Quality‐of‐life parameters provide prognostic survival information over and above what is provided by clinical and sociodemographic variables. Although clinicians tend to view quality of life as a soft endpoint, there is a wealth of information that it can bring to clinicians; and, as such, quality of life is gaining momentum.